Valence, Arousal, and Cognitive Control: A Voluntary Task-Switching Study - Demanet, Jelle; Liefooghe, Baptist; Verbruggen, Frederick (Frontiers in Psychology, 2011)
The present study focused on the interplay between arousal, valence and cognitive control. To this end, we investigated how arousal and valence associated with affective stimuli influenced cognitive flexibility when switching between tasks voluntarily. Three hypotheses were tested. First, a valence hypothesis that states that the positive valence of affective stimuli will facilitate both global and task-switching performance because of increased cognitive flexibility. Second, an arousal hypothesis that states that arousal, and not valence, will specifically impair task-switching performance by strengthening the previously executed task-set. Third, an attention hypothesis that states that both cognitive and emotional control ask for limited attentional resources, and predicts that arousal will impair both global and task-switching performance. The results showed that arousal affected task-switching but not global performance, possibly by phasic modulations of the noradrenergic system that reinforces the previously executed task. In addition, positive valence only affected global performance but not task-switching performance, possibly by phasic modulations of dopamine that stimulates the general ability to perform in a multitasking environment.